Isolation and Expression Analysis of the Flavanone 3-Hydroxylase Genes in Lotus (Nelumbo nucifera gaertn.), Waterlily (Nymphaea sp.) and Transient Silencing in Waterlily - Chaivarakun Chaipanya (Science Faculty of Chiang Mai University, 2019)
Flavanone 3-hydroxylase (F3H) converts flavanones from dihydroflavonols, which leads to production of flavonoid compounds via the anthocyanin biosynthesis pathway in plants. In this study, the F3H gene was isolated from lotus (Nelumbo nucifera Gaertn.) cv. Buntharik (white petal lotus), cv. Satabankacha (pink petal lotus), and waterlily (Nymphaea sp.) var. St. Louis Gold by reverse transcription PCR (RT-PCR). The open reading frames (ORF) of three cultivars’ genes were 1,134 bp in length, encoding a predicted protein of 377 amino acids. Their nucleotide sequences were identical, and the amino acid sequence shared high homology to F3H from different plant species. Expression of F3H was specifically regulated in petals and stamens, while less expression was found in leaf tissue of waterlily variety St. Louis Gold. The correlation of F3H expression according to specific colouration was performed in waterlily. The F3H gene was more highly expressed in decreasing order of red, purplish blue, and yellow petals when compared using semi quantitative PCR (sqPCR). Gene regulation according to flowering stage and pigmentation was determined in lotus. The F3H expression was slightly diminished in petals of cultivar Satabankacha at the fully-opening stage, whereas it was detected in the cultivar Buntharik only when white petals were tinted with pink. An RNAi gene-silencing vector, pJA8F3H, encoding a hairpin F3H RNA, was introduced to waterlily petals using the Agrobacterium infiltration method, and the F3H expression was analysed at 1 and 3 days post infiltration (dpi) by sqPCR. The results showed that the F3H expression was down-regulated at 3 dpi in flowers tested of the red petal variety and purplish blue petal variety compared to controls. The results confirmed that pJA8F3H is efficient and could be used as a transformation vector to transiently suppress F3H expression in waterlily or lotus.